The life of Lazarillo de Tormes = La vida de Lazarillo de Tormes y de sus fortunas y adversidades - Rowland, David, active 1569-1586; Whitlock, Keith (Hispanic classics., 2000)
"This is the first scholarly edition of David Rowland of Anglesey's 1586 translation of Lazarillo de Tormes (1554). The purpose is to make available one of the most important and influential translations into early modern English, which has had a profound effect upon the evolution of English prose fiction and the characterization of English Renaissance drama." "Lazarillo de Tormes was one of the first early modern Europe wide best-sellers. Ostensibly a racy autobiography of a young rogue and his succession of masters, in reality it is a comical and caustic expose of sixteenth century Spanish society, and especially the Church. Rowland's translation exploited the propaganda potential of the text at a time when England and Spain drifted into open war." "This edition will prove invaluable to those teaching European Renaissance studies, English Renaissance drama and English prose fiction, and has been specially prepared for The Open University course: AA305 The Renaissance in Europe: A Cultural Enquiry."--Jacket